Decoding Criminal Minds: A Study of Criminal Profiling Methods and the Forensic Science Investigation in the Criminal Justice System in India - Nidhi, M.; Kumar, Prashant (Journal of Neonatal Surgery, 2025)
Criminal profiling is a process where the end result of the actions of an offender is inverted to rebuild their personality and motives. This method assists the police in their work by guessing the logic of crime, which makes the investigation more effective. Crime and criminals in India have been a major problem to law enforcement and there is an immediate need to enhance criminal profiling methods. The existing approaches such as social, economic, anthropological and psychodynamic approaches have their limitations. By 2023, 427 rape, sexual assault, POCSO, and homicide cases samples were in await, which showed that the system was inefficient. According to the Forensic Science India Report, the problems in the forensic labs are systemic, including poor infrastructure, understaffing, and absence of standard operating procedures. Between 2013 and 2018, 40.3 percent of authorized posts in forensic laboratories were empty and this affects the efficiency and speed of criminal trials and the judicial system. The purpose of this paper is to connect law and human behavior through the analysis of the behavioral patterns applicable to the criminal profiling. It attempts to present the information on criminal penology in India and give suggestions on how to improve it. The important elements of profiling like the crime scene analysis, behavior analysis, victimology, geographical profiling, and psychological profiling shall also be mentioned. Such approaches as inductive and deductive reasoning and the combination of profiling and law enforcement will also be discussed. The idea is to improve the validity and use of criminal profiling in the legal system and it is presently known that the research and assessment should continue. Criminal profiling is an effective instrument in crime investigations as it aids in comprehending the actions of the offenders, reduces the size of the suspects and focuses on the investigation process. Nonetheless, there is a necessity to critically assess and keep on enhancing profiling methods. The criminal justice system can be strengthened through addressing the challenges in the forensic science laboratories and improving the profiling methodologies that will help in improving the speed and accuracy of criminal investigations in India